Weekly Low-Dose Paclitaxel as Maintenance Treatment in Patients With Advanced Ovarian Cancer Who Had Microscopic Residual Disease at Second-Look Surgery After 6 Cycles of Paclitaxel/Platinum-Based Chemotherapy: Results of an Open Noncomparative Phase 2 Multicenter Italian Study (After-6 Protocol 2). Issue 4 (1st April 2009) - Gadducci, Angiolo; Katsaros, Dionyssios; Zola, Paolo; Scambia, Giovanni; Ballardini, Michela; Pasquini, Enzo; Fertonani, Carlo; Maggi, Lorenzo; Pecorelli, Sergio; Conte, Pier Franco; ,
Abstract : The aim of this paper was to assess whether weekly intravenous 60-mg/m 2 paclitaxel for 21 weeks is feasible and effective as maintenance treatment in 64 patients with advanced ovarian cancer who had microscopic residual disease after 6 cycles of paclitaxel/platinum-based chemotherapy. Forty-eight patients completed the planned cycles of weekly paclitaxel. The worst toxicities were grade 2 leukopenia in 22.4% of the patients, grade 2 neutropenia in 25.9%, grade 2 sensorial neurotoxicity in 20.7%, and grade 2 motor neurotoxicity in 6.9%. Seventeen patients underwent a third-look surgery that showed a pathological complete response in 6 (35.3%, 95% confidence interval [CI], 17.3%-59.0%) cases. The 3-year progression-free survival rate was 18% (95% CI, 9.6%-33.8%), and the 3-year overall survival rate was 64% (95% CI, 52.0%-78.0%). Weekly low-dose paclitaxel is a feasible and well-tolerated maintenance treatment.